9x-3=-2x-18

Simple and best practice solution for 9x-3=-2x-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-3=-2x-18 equation:


Simplifying
9x + -3 = -2x + -18

Reorder the terms:
-3 + 9x = -2x + -18

Reorder the terms:
-3 + 9x = -18 + -2x

Solving
-3 + 9x = -18 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-3 + 9x + 2x = -18 + -2x + 2x

Combine like terms: 9x + 2x = 11x
-3 + 11x = -18 + -2x + 2x

Combine like terms: -2x + 2x = 0
-3 + 11x = -18 + 0
-3 + 11x = -18

Add '3' to each side of the equation.
-3 + 3 + 11x = -18 + 3

Combine like terms: -3 + 3 = 0
0 + 11x = -18 + 3
11x = -18 + 3

Combine like terms: -18 + 3 = -15
11x = -15

Divide each side by '11'.
x = -1.363636364

Simplifying
x = -1.363636364

See similar equations:

| 7(4x+9)=6(11x-12) | | 7x(4x+9)=6(11x-12) | | -106-10x=9x+20 | | 3p+6m=3m-9 | | 8x-9y=-16 | | 9x-6=10x+12 | | 9(x+2)+6(x+6)=6x-6 | | 71.80=25+0.15 | | 4y+3y=11 | | -x-3y=-23 | | x+4-3x^2=0 | | 3-2x+x=5x-5+2x | | 8w-32=4w | | -7-x=3x+17 | | 2x^2-50=24 | | 1x-4+1x=5(9-4x) | | 2-8x+1(x-4)=2(x-7) | | 6x+3=2x+31 | | m-14.6=9.74 | | 4+2x=5x-2 | | w-8=32 | | 4y-8=5y-1 | | 17dl=l | | 3x+4=-36-5x | | x=2*8+77 | | 16+5x= | | 3x+4=-35-5x | | (2x+5)x(7x-2)=(4x+3)x(5x-1)+82 | | 4(d-7)=524 | | X-4X+3Y+9Y-12=0 | | 5x+3x+120=360 | | 6*x*y-12=0 |

Equations solver categories